Authentication as Institutional Maintenance Work. (16th December 2018) - Colombero, Sylvain; Boxenbaum, Eva
Abstract: Institutional maintenance work refers to actors' deliberate effort to maintain an institution. This paper examines how actors use authentication, i.e., the relational constitution of an artefact as original or as a genuine expression of a particular type, style or person, to accomplish institutional maintenance work. We investigated contemporary adjustments to six listed buildings. These works were undertaken to keep these buildings functional while at the same time protecting their listing; by doing so they contributed to maintain the institution of Architectural Heritage. Our analysis identifies three forms of authentication: material consolidation, crafts mobilization and character enhancement. We elaborate on each of them and explain their institutional underpinnings and outcomes. The paper concludes with an articulation of authentication as a potent form of institutional maintenance work. Taking its starting point in materiality, authentication is a relational practice that helps maintain institutions relying on irreplaceable artefacts for their maintenance.